Class II human leucocyte antigen DRB1*11 in hairy cell leukaemia patients with and without haemolytic uraemic syndrome. (13th June 2014) - Arons, Evgeny; Adams, Sharon; Venzon, David J.; Pastan, Ira; Kreitman, Robert J.
Summary Frequencies of human leucocyte antigens (HLA) were determined in 287 classic hairy cell leukaemia (HCL) patients. With respect to both population (n = 287) and allele (2n = 574) frequency respectively, the most common HLA class I and II antigens expressed were HLA‐A*02 (49·1% and 28·6%), HLA‐B*07 (21·3% and 11·1%), HLA‐C*07 (46·7 and 28·2%), HLA‐DQB1*03 (62·7% and 37·3%), HLA‐DRB1*11 (30·0% and 16·0%) and HLA‐DRB4*01 (45·3% and 29·6%). In comparing 6–14 databases of control Caucasians to 267 Caucasian HCL patients, only HLA‐DRB1*11 was consistently over‐represented in HCL, 31·1% of patients vs. 17–19·9% of controls (P = 0·0055 to <0·0001) and 16·5% of alleles vs. 6·5–12·3% of control alleles (P = 0·022 to <0·0001). HLA‐DRB1*11 is a known risk factor for acquired thrombotic microangiopathy. Anti‐CD22 recombinant immunotoxin BL22 in HCL was associated with a 12% incidence of completely reversible grade 3–4 haemolytic uraemic syndrome (HUS), mainly during the second or third retreatment cycle. Of 49 HCL patients receiving ≥2 cycles of BL22, 7 (14%) had HUS and HLA‐DRB1*11 was expressed in 71% of 7 with HUS compared with only 21% of 42 without (P = 0·015). These data suggest that DBR1*11 may be a marker for increased susceptibility to HCL and, among HCL patients, could be a risk factor for BL22‐induced HUS.